2019
DOI: 10.1038/s41598-019-51620-z
|View full text |Cite
|
Sign up to set email alerts
|

A Low Cost and Portable Microwave Imaging System for Breast Tumor Detection Using UWB Directional Antenna array

Abstract: Globally, breast cancer is a major reason for female mortality. Due to the limitations of current clinical imaging, the researchers are encouraged to explore alternative and complementary tools to available techniques to detect the breast tumor in an earlier stage. This article outlines a new, portable, and low-cost microwave imaging (MWI) system using an iterative enhancing technique for breast imaging. A compact side slotted tapered slot antenna is designed for microwave imaging. The radiating fins of tapere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(101 citation statements)
references
References 51 publications
0
84
0
Order By: Relevance
“…In 2019, Islam et al developed a portable breast imaging unit comprising nine side-slotted tapered slot antennas as seen in Fig. 4(a) [111]. The Iteratively Corrected Delay Multiply and Sum (IC-DAS) algorithm played a decisive role in the reconstruction [112].…”
Section: Signal Acquisitionmentioning
confidence: 99%
“…In 2019, Islam et al developed a portable breast imaging unit comprising nine side-slotted tapered slot antennas as seen in Fig. 4(a) [111]. The Iteratively Corrected Delay Multiply and Sum (IC-DAS) algorithm played a decisive role in the reconstruction [112].…”
Section: Signal Acquisitionmentioning
confidence: 99%
“…Table 1 shows the dielectric properties of breast phantom and tumor used in this research, mimicking the dielectric properties of real human breast. The experimental setup used in this work is similar to the approach used in works discussed in [ 25 ] and [ 26 ]. Such setup has shown that certain type of containers are still being used to hold the breast phantom during the measurement.…”
Section: Data Collectionmentioning
confidence: 99%
“…In real time field conditions, an antenna array will be set around the head, and reflected signals will be collated and processed by digital signal processing algorithms. The collated signals can then be visualized as a 2D image using digital image processing algorithms [23,24]. This antenna might be a basis for a futuristic diagnostic tool for point-of-care stroke detection by the first responders.…”
Section: Resultsmentioning
confidence: 99%